Investigation of root apical closure of first permanent molars with cone-beam computed tomography: A retrospective study - Fahrettin Kalabalık; Neslihan Yılmaz; Elif Gül Aydın; Emre Aytuğar (Elsevier, 2024)
Background/purpose: The objective of this study was to assess the root apical closure ages of first permanent molars retrospectively among a group of western Turkish children aged between 5 and 15 years using cone-beam computed tomography (CBCT). Materials and methods: CBCT images of 202 patients were examined. The patients were divided into 7 groups according to age: ≤8 years, 8-8.99 years, 9-9.99 years, 10-10.99 years, 11-11.99 years, 12-12.99 years, and ≥13 years. Teeth with at least one open apex were considered as 'teeth with open apex' and teeth with all closed apices were considered as 'teeth with closed apex'. The data was evaluated by Pearson Chi-square test and Fisher's exact test. P value of <0.05 was considered statistically significant. Results: Apical closure rate of the maxillary first molars was 4.1%, 32.2%, 55.4%, 76.2%, and 90.6% at 8-8.99 years, 9-9.99 years, 10-10.99 years, 11-11.99 years, and 12-12.99 years, respectively. Apical closure rate of the mandibular first molars was 4.4%, 41.2%, 70.7%, 80.0%, and 92.2% at 8-8.99 years, 9-9.99 years, 10-10.99 years, 11-11.99 years, and 12-12.99 years, respectively. At 12-12.99 years, females had a significantly higher rate of closed root apices of mandibular first molars than males (P < 0.05). At 9-9.99 and 12-12.99 years, females had a significantly higher rate of closed root apices of maxillary molars than males (P < 0.05). Conclusion: CBCT is a useful tool for the evaluation of root development. The results of present study can provide valuable aids for clinicians during root canal treatment of permanent first molars.